Co-expression of Argonaute2 Enhances Short Hairpin RNA-induced RNA Interference in Xenopus CNS Neurons In Vivo - Chen, Chih-ming; Chiu, Shu-Ling; Shen, Wanhua; Cline, Hollis (Frontiers in Neuroscience, 2009)
RNA interference (RNAi) is an evolutionarily conserved mechanism for sequence-specific gene silencing. Recent advances in our understanding of RNAi machinery make it possible to reduce protein expression by introducing short hairpin RNA (shRNA) into cells of many systems, however, the efficacy of RNAi-mediated protein knockdown can be quite variable, especially in intact animals, and this limits its application. We built adaptable molecular tools, pSilencer (pSi) and pReporter (pRe) constructs, to evaluate the impact of different promoters, shRNA structures and overexpression of Ago2, the key enzyme in the RNA-induced silencing complex (RISC), on the efficiency of RNAi. The magnitude of RNAi knockdown was evaluated in cultured cells and intact animals by comparing fluorescence intensity levels of GFP, the RNAi target, relative to mCherry, which was not targeted. Co-expression of human Ago2 with shRNA significantly enhanced efficiency of GFP knockdown in cell lines and in neurons of intact Xenopus tadpoles. Human H1- and U6-promotors alone or the U6-promotor with an enhancer element were equally effective at driving GFP knockdown. shRNA derived from the microRNA-30 design (shRNAmir30) enhanced the efficiency of GFP knockdown. Expressing pSi containing Ago2 with shRNA increased knockdown efficiency of an endogenous neuronal protein, the GluR2 subunit of the AMPA receptor, functionally accessed by recording AMPA receptor-mediated spontaneous synaptic currents in Xenopus CNS neurons. Our data suggest that co-expression of Ago2 and shRNA is a simple method to enhance RNAi in intact animals. While morpholino antisense knockdown is effective in Xenopus and Zebrafish, a principle advantage of the RNAi method is the possibility of spatial and temporal control of protein knockdown by use of cell type specific and regulatable pol II promoters to drive shRNA and Ago2. This should extend the application of RNAi to study gene function of intact brain circuits.